If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(5x-4)=3(6x+5)
We move all terms to the left:
6(5x-4)-(3(6x+5))=0
We multiply parentheses
30x-(3(6x+5))-24=0
We calculate terms in parentheses: -(3(6x+5)), so:We get rid of parentheses
3(6x+5)
We multiply parentheses
18x+15
Back to the equation:
-(18x+15)
30x-18x-15-24=0
We add all the numbers together, and all the variables
12x-39=0
We move all terms containing x to the left, all other terms to the right
12x=39
x=39/12
x=3+1/4
| 3h+4=28 | | 3/2+16/15=w | | 8x+3x=-11 | | 5(7-x)=31x | | (1÷2x-5)+(15÷2x-1)=2 | | 10+4y=30 | | X+1-2=x16 | | 2x/5+23/5=3 | | 4x/3+23/3=17 | | 6(4x+1)=74 | | 38-4+m=48 | | 6x/4=58 | | 84=x+(x*x*x) | | (2x+3)(3x+1)=1 | | 36^3x=1/216 | | 59=7u | | 4x-12/3=16 | | 4^3m=16 | | q=2/5=2q-11/7 | | 3(5x-(2-x))=12x | | 2x-3x+15=7 | | 2(1+3(2+x))=4x | | (2-8)(-3)=5x | | |2x-11|=39 | | (53^x)=20 | | 53^x=20 | | 14/f=2 | | x+(x+1)+(x+3)=51 | | (x-7)^2=-3 | | (3x+2)=2.6 | | (6x+7)^1/2=x-8 | | 5(x-1)-3=13 |